(untitled) (Nigerian Journal of Pharmaceutical Research, 2021)
Background:Tephrosia bracteolata is a widespread shrub belonging to the family (Fabaceae) and genus Tephrosia. It is traditionally used for treating rheumatic pains, dropsy and stomach ache. Objectives:In view of the ethnomedicinal claim and the continuous search for new medicinal agents, the phytochemical constituents, analgesic and anti-inflammatory activities of chloroform fraction (CF) of the methanol extract of Tephrosia bracteolata in mice and rats was evaluated. Methods:Preliminary phytochemical screening was conducted using standard method. Analgesic activity of CF (100, 200 and 400 mg/kg body weight orally) was investigated using acetic acid-induced writhing test and thermally induced pain model in mice. Additionally, anti-inflammatory activity was tested by carragenaan-induced paw edema in rats. Results:Phytochemical screening revealed the presence of alkaloids, triterpenes and flavonoids. The oral LD50 of CF was above 2000 mg/kg body weight. CF significantly (p<0.05) and dose dependently reduced the number of writhes with percentage inhibition of 47.76 48.41 and 72.6 % at dose of 100, 200 and 400mg/kg respectively. CF also significantly (p<0.05) and dose dependently increased the mean reaction time. At dose of 400 mg/kg, CF at 60 and 90 minutes exhibited greater activity when compared to the standard agent pentazocine. CF(200 and 400 mg/kg) at times 3, 4 and 5 hours significantly (p<0.05) decreased the paw edema in rats when compare with the ibuprofen treated group. Conclusions:The chloroform fraction of the methanol crude extract of Tephrosia bracteolata possesses analgesic and anti-inflammatory activities.